1999
DOI: 10.1159/000045487
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profiles in Patients with Atherosclerotic Renal Artery Stenosis

Abstract: Background: Atherosclerotic renal artery stenosis (ARAS) is an important cause of renal disease in the elderly, and these patients have a high morbidity and mortality. There are no data on their blood lipid profiles. Methods: The lipoprotein profiles were examined in patients with proven ARAS and compared with patients matched for age, gender, renal function and presence of diabetes. Results: The profiles did not show any significant difference for apolipoprotein B (control 1.31 ± 0.39 vs. ARAS 1.24 ± 0.28; me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…Scoble et al [81] examined the lipoprotein profiles in patients with proven ARAS and compared them with patients matched for age, gender, renal function and the presence of diabetes. Although no significant difference was demonstrated for apolipoprotein B, cholesterol, LDL cholesterol, fibrinogen, high-density lipoprotein cholesterol and triglyceride levels between the groups, the serum Lp(a) levels were higher in the control group (compared with the ARAS group; 58 ± 45 vs. 31 ± 21 mg/dl, respectively; p < 0.01).…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Scoble et al [81] examined the lipoprotein profiles in patients with proven ARAS and compared them with patients matched for age, gender, renal function and the presence of diabetes. Although no significant difference was demonstrated for apolipoprotein B, cholesterol, LDL cholesterol, fibrinogen, high-density lipoprotein cholesterol and triglyceride levels between the groups, the serum Lp(a) levels were higher in the control group (compared with the ARAS group; 58 ± 45 vs. 31 ± 21 mg/dl, respectively; p < 0.01).…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…However, another study that reported higher homocysteine levels in patients with ARAS than healthy controls could not demonstrate any significant change in these levels 6 months after renal angioplasty [45], therefore questioning the relevance of homocysteine as an independent marker of ARAS. With regard to lipoprotein(a), findings are even more controversial because plasma levels in patients with ARAS have been reported to be higher [24], unchanged [21], or even lower [25] than in subjects without ARAS. A non-significant trend to increased lipoprotein(a) was reported in 26 hypertensive patients with secondary hypertension due to ARAS in comparison to patients with essential hypertension [46].…”
Section: Discussionmentioning
confidence: 99%
“…Among these conditions, elevated lipoprotein(a) levels and a prothrombotic state might be of particular interest because both have been shown to have specific relevance for the development of organ damage in hypertensive patients [19,20]. Previous studies have suggested a possible contribution to ARAS of plasma fibrinogen [21,22] and homocysteine [23] levels, whereas the role of lipoprotein(a) remains unclear [21,24,25], most likely because none of the studies conducted so far has been specifically designed to investigate its role. This study was designed to investigate whether plasma levels of lipoprotein(a) and hemostatic and fibrinolytic markers are associated with ARAS and can predict its presence in hypertensive patients.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only one previous study by Scoble et al [4] has specifically investigated lipid abnormalities in ARVD patients, although lipoprotein subclasses were not analyzed. These investigators found markedly reduced ApoA-I levels and as a consequence a lower ApoA-I/ApoB ratio in patients with ARAS who were not on lipid-lowering therapy, compared to matched control patients.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the increased CV mortality in this patient group is most likely multifactorial and may at least partially be a consequence of the generalized atherosclerotic burden. Still, other risk factors such as reduced glomerular filtration rate (GFR) [1] and dyslipidemia [4] may also be involved. In patients with atherosclerotic renovascular disease (ARVD), dyslipidemia could obviously be a primary event leading to the development of peripheral stenotic lesions involving renal arteries.…”
Section: Introductionmentioning
confidence: 99%